RECLASSIFYING CHINESE PHRASE STRUCTURES: FROM FORMAL CONFIGURATION TO SEMANTIC RELATIONS - Sun Jiaze; Mulyadi; Arga Lubis (Lire Journal (Journal of Linguistics and Literature), 2026)
The classification of Chinese phrase structures has traditionally been based on formal configuration, especially categories such as subject-predicate, verb-object, and modifier-head constructions. Although this approach is descriptively useful, it does not always explain why phrases with similar forms show different syntactic behavior, or why different forms may perform similar grammatical functions. This study therefore proposes a reclassification of Chinese phrase structures from formal configuration to semantic relations. Using a qualitative corpus-based descriptive design, the study analyzes 800 modern Chinese phrase tokens drawn from dictionaries, literary texts, news discourse, and linguistic studies. The findings show that semantic classification more effectively explains phenomena such as same form, different function, different form, same function, and form-meaning divergence. The study identifies core semantic relations, including agent-action, patient-action, instrument-action, location-action, object-action, restrictive, coordinative, and complementive relations, and demonstrates that these are closely related to sentence-convertibility, collocational compatibility, nominalization tendency, and ambiguity resolution. Through examples such as ???? (réncái ji?oliú), ???? (xuézh? t?olùn), ??? (shài tàiyáng), and ??? (xi? fángzi), the study argues that semantic relations provide a more adequate explanatory basis for Chinese phrase classification. It concludes that formal structure remains an important descriptive layer, while semantic relations offer a more explanatory framework for analysing Chinese phrase structures, especially in cases involving ambiguity, form–meaning divergence, and differences in syntactic behaviour.